RESEÑA de : Gonzalbes Cravioto, E. La ciudad romana de Valeria (Cuenca). Cuenca : Ediciones de la Universidad de Castilla-La Mancha, 2009 - Bailón García, Marta (Espacio Tiempo y Forma. Serie II, Historia Antigua, 2010)
-